Open to Disruption Time and Craft in the Practice of Slow Sociology - Garey, Anita Ilta; Nelson, Margaret K.; Hertz, Rosanna (Vanderbilt University Press, 2014)
At a time when an emphasis on productivity in higher education threatens to undermine well-crafted research, these highly reflexive essays capture the sometimes profound intellectual effects that may accompany disrupted scholarship. They reveal that over long periods of time relationships with people studied invariably change, sometimes in dramatic ways. They illustrate how world events such as 9/11 and economic cycles impact individual biographies. Some researchers describe how disruptions prompted them to expand the boundaries of their discipline and invent concepts that could more accurately describe phenomena that previously had no name and no scholarly history. Sometimes scholars themselves caused the disruption as they circled back to work they had considered "done" and allowed the possibility of rethinking earlier findings.